Pro-opiomelanocortin neurons in the nucleus of the solitary tract mediate endorphinergic endogenous analgesia in mice. Issue 5 (18th May 2023) - Patra, Pabitra Hriday; Tench, Becks; Hitrec, Timna; Holmes, Fiona; Drake, Robert; Cerritelli, Serena; Spanswick, David; Pickering, Anthony Edward
Abstract : Supplemental Digital Content is Available in the Text. Optogenetic and Chemogenetic activation of pro-opiomelanocortin neurons in the medulla produces sustained endorphinergic endogenous analgesia and chemogenetic inhibition demonstrates that they are necessary for stress-induced analgesia in mice. Abstract: The nucleus of the solitary tract (NTS) contains pro-opiomelanocortin (POMC) neurons that are 1 of the 2 major sources of β-endorphin in the brain. The functional role of these NTSPOMC neurons in nociceptive and cardiorespiratory function is debated. We have shown that NTSPOMC optogenetic activation produces bradycardia and transient apnoea in a working heart–brainstem preparation and chemogenetic activation with an engineered ion channel (PSAM) produced opioidergic analgesia in vivo. To better define the role of the NTSPOMC neurons in behaving animals, we adopted in vivo optogenetics (ChrimsonR) and excitatory/inhibitory chemogenetic DREADD (hM3Dq/hM4Di) strategies in POMC-Cre mice. We show that optogenetic activation of NTSPOMC neurons produces time-locked, graded, transient bradycardia and bradypnoea in anaesthetised mice that is naloxone sensitive (1 mg/kg, i.p.), suggesting a role of β-endorphin. Both optogenetic and chemogenetic activation of NTSPOMC neurons produces sustained thermal analgesia in behaving mice that can be blocked by naloxone. It also produced analgesia in an inflammatory pain model (carrageenan) but not in a neuropathic pain model (tibial nerve transection). Inhibiting NTSPOMC neurons does not produce any effect on basal nociception but inhibits stress-induced analgesia (unlike inhibition of arcuate POMC neurons). Activation of NTSPOMC neuronal populations in conscious mice did not cause respiratory depression, anxiety, or locomotor deficit (in open field) or affective preference. These findings indicate that NTSPOMC neurons play a key role in the generation of endorphinergic endogenous analgesia and can also regulate cardiorespiratory function.